1996
DOI: 10.1046/j.1365-2141.1996.6912313.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and non‐Hodgkin's lymphomas

Abstract: Hepatitis C virus (HCV) seems to be the aetiologic agent of mixed cryoglobulinaemia, and as this 'benign' lymphoproliferative disorder can frequently develop into more aggressive haematological disorders, this study was undertaken to determine the prevalence of HCV infection in non-Hodgkin's lymphomas. 199 unselected subjects treated by three haematological centres in Northeast Italy were investigated for the presence of HCV infection. As controls, the prevalence of HCV infection was determined in a group of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
92
3
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(109 citation statements)
references
References 28 publications
(29 reference statements)
11
92
3
3
Order By: Relevance
“…Apart from Mazzaro et al, 34 who reported a higher prevalence of genotype 1b (70.2%), among the other 138 patients reported 57 (41.3%) were bearing genotype 2a/2ac and 56 (40.5%) genotype 1b, confirming our findings. In particular, this was observed among patients with B cell NHL complicating MC, 6 among patients with MC, 30 a lymphoproliferative disorder which is currently considered an expression of low-grade B cell NHL, 8 among patients with monoclonal gammopathies, 31,42 and among patients with B cell NHL complicating MC or arising 'de novo' (Refs 43, 44 and the present report).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from Mazzaro et al, 34 who reported a higher prevalence of genotype 1b (70.2%), among the other 138 patients reported 57 (41.3%) were bearing genotype 2a/2ac and 56 (40.5%) genotype 1b, confirming our findings. In particular, this was observed among patients with B cell NHL complicating MC, 6 among patients with MC, 30 a lymphoproliferative disorder which is currently considered an expression of low-grade B cell NHL, 8 among patients with monoclonal gammopathies, 31,42 and among patients with B cell NHL complicating MC or arising 'de novo' (Refs 43, 44 and the present report).…”
Section: Discussionsupporting
confidence: 91%
“…[16][17][18][19] On the contrary, genotype 2a is more likely to be found among apparently healthy blood donors than in patients with CLD, 32 or in patients with mild CLD or in those who respond better to IFN therapy. [12][13][14][15][16][17][18][19] HCV might be a causative cofactor in the pathogenesis of B cell NHL: it is found in a significative percentage of some histotypes of NHL, 8,11,33,34 it is known to be able to infect B lymphocytes circulating in the peripheral blood (PB) 35 or infiltrating the bone marrow (BM) 36 and the liver, 37 and in vitro studies have shown its ability to infect a human BM-derived B cell line and the PB MNC from healthy subjects. [38][39][40] If this is the case, it would appear appropriate to assess the prevalence of different HCV genotypes among the patients bearing a B cell NHL, with the aim of finding a possible correlation between a particular genotype and the lympho-proliferative disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies came from Italy, and studies from France, Japan, the United States, and England followed. HCV prevalence in these series was between 0.004% and 33% [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The lowest prevalence was found in a British study, where 1 out of 268 lymphoma patients had tumors positive for HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of peripheral blood mononuclear cells with HCV is a useful parameter in the pathogenesis of HCV infection [40]. Although some investigators believe HCV plays a role in the pathogenesis of NHL, some others refuse this explanation [8,9,25,26,30,[43][44][45]. The presence of viral material in lymphoma samples is not sufficient due to the lymphotropism of this virus.…”
Section: Discussionmentioning
confidence: 99%
“…At least eight investigations from Italy, including over 1300 patients, reported that approximately one-fourth (range 9-40%) of patients with B-cell NHL were positive for HCV antibodies (Ferri et al, 1994;Cavanna et al, 1995;Mazzaro et al, 1996;Musto et al, 1996;Pioltelli et al, 1996;Silvestri et al, 1996;De Rosa et al, 1997;Luppi et al, 1997). Although most studies did not include a control group, HCV positivity was many times higher than in agecomparable groups of the Italian population (i.e.…”
mentioning
confidence: 99%